Ugotavljanje avtorskih pravic na fotografijah z vidika spletnega repozitorija - Damjan, Matija (Pravni letopis, 2014)
When incorporating photographic works in a publicly accessible online repository, such as Wikimedia Commons, it is necessary to determine whether they are (still) protected by copyright. The article presents the conditions for copyright protection of photographic works and analyses the provisions of the existing and previous legislation on the duration of rights, with the aim to identify as clearly as possible the categories of photographic works no longer protected by copyright, taking into account the date of their creation or publication or of the author`s death. When another copyrighted work is depicted in the photograph, the rights of its author are also relevant. In this regard, the rules of freedom on panorama can come into play. The special protection of the image and the name of a cultural monument under the rules of cultural heritage protection is also discussed.
Keywords: avtorske pravice; digitalna fotografija; digitalni repozitoriji; fotografije